دور إدارة الصراع داخل فرق العمل في تعزيز التعلّم التنظيمي دراسة ميدانية في جامعة تشرين - ديب كندة; البهلول علي (Latakia University Journal - Economic and Legal Sciences Series, 2018)
The research aims to study the relationship between the role of conflict management within work teams on the one hand, and between the promotion of organizational learning in Tishreen University, on the other hand, where the researcher distributed a questionnaire to a sample of theoretical and applied colleges in Tishreen University amounted to (240) questionnaire was recovered (230) to identify them. To test the relationship, the researcher using the Student T test for one sample, as well as the Pearson correlation coefficient. The research by the study concluded that there is a rise in the level conflict management in the colleges under study, as well as a rise in the level of each of single and dual-loop learning in colleges under study. The research concluded that there were significant relationship between conflict management within teams, and organizational learning at Tishreen University, and thus the existence of the role of conflict management within teams in enhancing organizational learning in the theoretical and applied colleges in Tishreen University. The research found a set of recommendations and proposals that will contribute positively to the role of conflict management within teams in promoting organizational learning. هدف البحث إلى دراسة العلاقة بين دور إدارة الصراع داخل فرق العمل من جهة، وبين تعزيز التعلم التنظيمي في جامعة تشرين من جهة ثانية، حيث قام الباحث بتوزيع استبانة على عينة من الكليات النظرية والتطبيقية في جامعة تشرين بلغت (240) استبانة تم استرداد (230) استبانة منها. ولاختبار العلاقة قام الباحث باستخدام اختبار T ستيودنت لعينة واحدة، وكذلك معامل ارتباط بيرسون. توصل البحث من خلال الدراسة إلى أن هناك ارتفاع في مستوى إدارة الصراع في الكليات محل الدراسة، وكذلك ارتفاع في مستوى كل من التعلم أحادي وثنائي الحلقة في الكليات محل الدراسة. كما توصل البحث إلى وجود علاقة معنوية بين إدارة الصراع داخل فرق العمل، والتعلم التنظيمي في جامعة تشرين، وبالتالي وجود دور لإدارة الصراع داخل فرق العمل في تعزيز التعلم التنظيمي في الكليات النظرية، والتطبيقية في جامعة تشرين. وخلص البحث إلى مجموعة من التوصيات والمقترحات من شأنها أن تسهم بشكل إيجابي بدور إدارة الصراع داخل فرق العمل في تعزيز التعلم التنظيمي.